Simulasi Penurunan Kadar Asam Askorbat Buah Jambu Biji (Psidium Guajava L.) Selama Penyimpanan Menggunakan Visual Basic 6.0 - Annisa Azzahra; Ratna Ratna; Agus Arip Munawar (Fakultas Teknik, 2021)
Technological advances continue to develop rapidly and people need technology that is more efficient and faster in their work, including in the field of agriculture. Therefore, simulation is a suitable way to be implemented in the scope of modern society. This study aims to reduce the number of research and experimental trials in the laboratory because it takes a lot of time and money. This research refers to a simulation of decreasing levels of ascorbic acid in guava fruit during the storage period which is carried out by presenting data obtained from various sources, programming and simulation design using Visual Basic 6.0 and program testing. Guava fruit (Psidium guajava L) has vitamin C content about 183.5 mg / 100 grams of material. The test results of this program, within 10 days of storage at room temperature (25oC) the levels of Ascorbic Acid in Guava fruit decreased by 56.1% and decreased levels of Ascorbic Acid by 92.26%, from 183.5 mg / 100 gr to around 12, 84 mg / 100 gr guava fruit for 720 hours. Therefore, the results of this simulation program succeeded in approaching the real number of decreases in ascorbic acid levels tested in original observations.